2003
DOI: 10.1111/j.1540-8159.2003.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillator Events in Patients with Asymptomatic Nonsustained Ventricular Tachycardia:

Abstract: Primary prevention trials have demonstrated that patients with coronary disease, reduced left ventricular function, and nonsustained ventricular tachycardia (NSVT) have improved survival with implantable cardioverter defibrillator (ICD) therapy, presumably secondary to effective termination of life-threatening arrhythmias. However, stored intracardiac electrograms were not always available and specific arrhythmias leading to ICD therapy were not always known. We examined the occurrence of ICD events in 51 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…22 Inappropriate therapies due to misclassification of rapidly conducted SVTs occurred in 15% of both patient groups and accounted for more than one third of all therapies and Ϸ40% of all shocks in both groups. Although SVT discrimination was equivalently underutilized in the minority of patients with single-chamber ICDs in both groups, this is consistent with the reported rates of inappropriate therapies in other trials of secondary 16,23,24 and primary 16,19,21 prevention. These observations emphasize that despite increasingly sophisticated enhancements to single-and dual-chamber ICD systems that rely on rate-based detection, rejection of SVT while maintaining high sensitivity for true ventricular arrhythmias remains elusive.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…22 Inappropriate therapies due to misclassification of rapidly conducted SVTs occurred in 15% of both patient groups and accounted for more than one third of all therapies and Ϸ40% of all shocks in both groups. Although SVT discrimination was equivalently underutilized in the minority of patients with single-chamber ICDs in both groups, this is consistent with the reported rates of inappropriate therapies in other trials of secondary 16,23,24 and primary 16,19,21 prevention. These observations emphasize that despite increasingly sophisticated enhancements to single-and dual-chamber ICD systems that rely on rate-based detection, rejection of SVT while maintaining high sensitivity for true ventricular arrhythmias remains elusive.…”
Section: Discussionsupporting
confidence: 78%
“…16 Additionally, some studies have reported that the cycle lengths of appropriately detected VT may be longer in secondary than in primary prevention patients 16 and that the difference in cycle lengths between appropriately detected VT and inappropriately detected SVT may be greater in primary prevention patients. 16,21 One possible interpretation of these data are that rate-based programming to achieve the optimal balance between VT detection and SVT rejection is different between primary and secondary prevention patients. This is not supported by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the PREPARE (Primary Prevention Parameters Evaluation) study was to adapt these strategies specifically to primary prevention patients both with and without Bi-V ICD indications. A treatment rate cutoff of 188 beats/min has been used to treat primary prevention patients in several large trials (2,6,15). In the latter 2 studies, investigators recommended a treatment cutoff between 170 and 180 beats/min for primary prevention patients in order to reduce the proportion of inappropriate therapies while still providing appropriate therapy.…”
mentioning
confidence: 99%
“…21 These patients are those most likely to benefit from discrimination algorithms because lower programmed VT detection rates result in increased risk of unnecessary therapy for SVT.…”
Section: Detection Of Svtmentioning
confidence: 99%